Fortalecimiento de la calidad de vida en el adulto mayor de la fundación San Alfonso María de Ligorio del municipio de Sibundoy- Putumayo. - Gaviria Garces, Cilena; Diaz Martinez, Angie Lorena (Universidad Antonio Nariño, 2021)
A study was carried out with the elderly of the San Alfonso María De Ligorio Foundation in the municipality of Sibundoy-Putumayo, in the year 2019-2020, the intention of this article is to be able to analyze the current reality of the proposition mentioned according to its relationship against the following categories of social well-being, family well-being, mental health and physical health. According to the above, the purpose of the research is to implement various activities that are aimed at strengthening the quality of life, through a qualitative paradigm, from the epistemological approach with type of study, action research, type of descriptive research. The unit of analysis consists of 21 older adults aged between 50 and 100 years. According to gender, there are 13 men (62%) and 8 women (38%); (29%), that is, 6 of them belong to indigenous communities. The results obtained through the semi-structured interview show the importance of working on weaknesses. For this, various activities were implemented in order to work each of the categories (social, family, mental and physical), and thus promote and raise the quality of life of the residents of the elderly; In the development of each exercise, observation was applied to recognize and identify attitudes and behavior of each older adult.